Photovoltaic-assisted thermoelectric cooling and heating systems - Irshad, K. (Springer Verlag, 2018)
At present, maintaining thermal comfort inside the buildings is becoming expensive and environmental unfriendly for a great majority of countries, as the mechanism of cooling air can prompt the tremendous utilization of energy and CO2 emissions. This chapter introduces the renewable concept of photovoltaic (PV) and thermoelectric module (TEM) implemented on the building for thermal load reduction. The chapter starts by describing the basics of the PV technology and its dependent parameters, which enhances its performance. In addition, TEMs as an alternative to conventional space conditioning technology are presented. Since PV panel can power the TEMs directly and cause no harm to the environment, therefore, the numerical modeling of PV-assisted TEMs for development of energy-efficient buildings is presented. After that, different kinds of literature focusing on the application of integration of two materials, i.e., TEM and PV for thermal load reduction of buildings, are provided. Results suggested that implementation of PV-assisted TEM system reduces 5â10 Â°C inlet temperature with COP ranges from 0.4 to 2.5. Lastly, the challenges and future commendation of PV-assisted TEMs technologies are discussed. Thus, it was suggested that PV-assisted TEM system provides Freon free, less energy consuming, and less CO2 emission solution to the space conditioning problem of the building as compared to traditional air-condition system. Â© Springer Nature Singapore Pte Ltd. 2018.